A Comparative Study of the Shafi‘i and Maliki Schools on Debt Transactions in the Mulangin Tradition within the Wedding Reception Culture of the Betawi Community - Fatih Zein Muhammad; Ahmad Bisyri Abd. Shomad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study examines the mulangin tradition within the Betawi community, a form of reciprocal social-economic practice that functions as an informal debt system rooted in solidarity and mutual aid. The problem arises from its unclear legal status in Islamic jurisprudence whether mulangin constitutes a lawful loan or a customary social practice. This research using a qualitative narrative and socio-legal approach, this research analyzes the practice through the perspectives of the Shafi‘i and Maliki schools, employing field interviews, observations, and classical fiqh texts as primary sources. The findings show that the Shafi‘i school emphasizes contractual clarity and the avoidance of additional benefits that could lead to Riba, while the Maliki school legitimizes mulangin as a valid social custom as long as it aligns with the objectives of Islamic law and mutual consent. The study concludes that mulangin represents a living synthesis between Islamic law and local wisdom, demonstrating the adaptability of Islamic jurisprudence in accommodating social and cultural realities without compromising the principles of justice , consent, and communal welfare.